Analysis Of Public Sentiment Towards The Corruption Eradication Commission On Twitter - Siti Nurhaliza Sofyan; Sri Wahyuni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The Corruption Eradication Commission (KPK) is a state institution in Indonesia which was formed to eradicate corruption. The Corruption Eradication Committee (KPK) [1]has the main task of carrying out investigations, inquiries and prosecutions of criminal acts of corruption. This institution is independent and free from the influence of any power in carrying out its duties and authority [2]. This research explores the analysis of Indonesian people's sentiment towards the KPK in the current situation such as arrests for corruption and the policies and actions carried out by the KPK. Sentiment analysis used in the journal with data obtained from Twitter data and using Orange Data Mining, with multilingual sentiment analysis techniques to analyze Indonesian people's sentiment towards the KPK agency. The results of sentiment analysis are visualized through box plots and scatter plots, which aim to classify Twitter users based on their emotional responses. The findings of this research provide valuable insight into the landscape of sentiment surrounding the Corruption Eradication Commission's bicycles, as well as providing sustainable benefits and are expected to be used as material for evaluating the government's role. Data totaling 300 tweets were processed using text mining techniques in the Orange Data Mining application [3][4]. This technique consists of several stages of text processing, namely transformation, filtering, and tokenization. The text processing results are extracted via wordcloud to find out the features of words that are often discussed by the public. After that, sentiment analysis was carried out to determine public opinion regarding the KPK institution based on positive, negative and neutral categories [5], [6]